Boosting Luminance Energy Transfer Efficiency in Upconversion Nanoparticles with an Energy‐Concentrating Zone. (25th July 2019) - Zhang, Xiaobo; Chen, Weiwei; Xie, Xiaoyu; Li, Yuyi; Chen, Desheng; Chao, Zhicong; Liu, Chenghui; Ma, Haibo; Liu, Ying; Ju, Huangxian
Abstract: Despite the successful application of upconversion nanoparticles (UCNPs), their low energy transfer efficiency is still a bottleneck to further applications. Here we design UCNPs with a multilayer structure, including an inert NaYF4 :Gd core and an energy‐concentrating zone (ECZ), for efficient energy concentration. The ECZ is composed of an emitting layer of NaYF4 :Yb, Er and an absorption layer of NaYF4 :Nd, Yb with antenna IRDye 800CW to manipulate the energy transfer. The stable and tight packing of 800CW linked originally with a bisphosphonate ligand improves greatly the transfer efficiency. The proximity of the emitting layer to both surface antenna and accepter also decreases energy depletion. Compared to classical UCNPs, the ECZ UCNPs show 3600 times higher luminescence intensity with an energy transfer efficiency near 60 %. In proof‐of‐concept applications, this type of structure was employed for Hg 2+ detection and for photodynamic therapy under hypoxic conditions. Abstract : Bitte etwas Konzentration ! Aufkonvertierende Nanopartikel (UCNPs) mit einer Energie‐konzentrierenden Zone erzielen eine effiziente Energiekonzentration. Sie zeigen exzellente Stabilität, 3600‐fache Lumineszenzverstärkung und eine Effizienz des resonanten Lumineszenzenergietransfers von 60 %. Als Eignungsnachweis wurden sie zur Hg 2+ ‐Detektion und photodynamischen Therapie unter hypoxischen Bedingungen eingesetzt.